The Underpinning Mechanism between Patience and Academic Procrastination: The Mediating Role of Self-Regulated Learning among Undergraduate Students - Wijaya, Hariz Enggar; Laili, Latifatul; Anshory, Adam (Perhimpunan Intelektual Muslim Indonesia, 2025)
Procrastination is a prevalent phenomenon in academic contexts. During online learning, the problem of postponing may become more prone to occur. Previous studies have shown that self-regulated learning has a robust effect on procrastination. However, researchers rarely consider the link between patience, self-regulated learning, and procrastination. This study investigated the role of patience and self-regulated learning on academic procrastination. We propose a mediation model that self-regulation would mediate the relationship between patience and procrastination. A total of 290 undergraduate students from a private university in Yogyakarta, Indonesia, enrolled in this study. There were 103 males and 187 females aged 17-24 (M=19.5 years). We collected the data by administering patience, self-regulated learning, and academic procrastination questionnaires. The result showed that patience, self-regulated learning, and procrastination were correlated significantly. Bivariate correlation showed patience positively and significantly associated with all self-regulated learning subscales: goal-setting, environmental structuring, time-management, help-seeking, self-evaluation, and task strategies. Furthermore, mediation analysis gives evidence that patience indirectly affects procrastination via student self-regulated learning. Only goal setting and time management could mediate the relationship between patience and academic procrastination at the specific indirect level. These findings highlight the role of patience in strengthening self-regulation and explain the underpinning mechanism between patience and procrastination.